2002
DOI: 10.1182/blood.v99.5.1659
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the antitumor properties of interleukin-2 by its targeted delivery to the tumor blood vessel extracellular matrix

Abstract: Angiogenic processes depend on the precise coordination of different cell types and a complex exchange of signals, many of which derive from new specific components of the provisional, angiogenesisrelated, extracellular matrix (ECM). Angiogenesis-associated ECM components thus represent appealing targets for the selective delivery of therapeutic molecules to newly forming tumor vessels. Results of a previous study indicated that a high affinity recombinant antibody (L19) to ED-B, a domain contained in the angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
277
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 262 publications
(287 citation statements)
references
References 38 publications
8
277
2
Order By: Relevance
“…Our group previously prepared a UG-free immunocytokine composed of IL2 and L19 and showed that its fusion with L19 enhanced the therapeutic index of the cytokine (11). This fusion protein is currently being investigated in a multicenter phase II clinical study in Italy and Germany (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group previously prepared a UG-free immunocytokine composed of IL2 and L19 and showed that its fusion with L19 enhanced the therapeutic index of the cytokine (11). This fusion protein is currently being investigated in a multicenter phase II clinical study in Italy and Germany (37).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained sequence was inserted into HindIII/NotI digested vector pcDNA3.1. We obtained the sequence encoding for the linker and IL2 by PCR from the construct pcDNA3.1/L19-IL2 as described in Carnemolla et al (11) using the primers TI-58 and TI-59. The cDNA fragment was inserted into NotI/XbaI-digested pcDNA3.1/L19-mUG to generate pcDNA3.1/L19-mUG-IL2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 In all experimental series, the loss of body weight for the 2 fusion proteins was comparable, and was less than 5% at all time points (V. Gafner, data not shown).…”
Section: Tumor Therapy Studies With P40-scfv(l19)/scfv(l19)-p35mentioning
confidence: 99%
“…L19 recognizes the alternatively spliced extra-domain B (EDB) of fibronectin (FN), a marker of angiogenesis (19). EDB-containing FN is present in the neovasculature of most solid tumors and hematologic malignancies (19) but absent from almost all healthy adult tissues (except tissues of the female reproductive cycle). Therefore, L19-IL2 represents a targeted form of IL2, which is able to accumulate at sites where angiogenesis occurs and the EDB-FN antigen is expressed.…”
Section: Introductionmentioning
confidence: 99%